Arachidonic Acid Derived Lipid Mediators Influence Kaposi’s Sarcoma-Associated Herpesvirus Infection and Pathogenesis - Chandrasekharan, Jayashree A.; Sharma-Walia, Neelam (Frontiers in Microbiology, 2019)
Kaposi’s sarcoma associated herpes virus (KSHV) infection, particularly latent infection is often associated with inflammation. The arachidonic acid pathway, the home of several inflammation and resolution associated lipid mediators, is widely altered upon viral infections. Several in vitro studies show that these lipid mediators help in the progression of viral pathogenesis. This review summarizes the findings related to human herpesvirus KSHV infection and arachidonic acid pathway metabolites. KSHV infection has been shown to promote inflammation by upregulating cyclooxygenase-2 (COX-2), 5 lipoxygenase (5LO) and their respective metabolites prostaglandin E2 (PGE2) and leukotriene B4 (LTB4) to promote latency and a pro-inflammatory microenvironment. Interestingly, the anti-inflammatory lipid mediator lipoxin is downregulated during KSHV infection to facilitate infected cell survival. These studies aid in understanding the role of arachidonic acid pathway metabolites in progression of viral infection, the host inflammatory response and pathogenesis. With limited therapeutic options to treat KSHV infection, use of inhibitors to these inflammatory metabolites and their synthetic pathways or supplementing anti-inflammatory lipid mediators could be an effective alternative therapeutic.